A natural bacterial-derived product, the metalloprotease arazyme, inhibits metastatic murine melanoma by inducing MMP-8 cross-reactive antibodies. - Felipe V Pereira; Carla A Ferreira-Guimarães; Thaysa Paschoalin; Jorge A B Scutti; Filipe M Melo; Luis S Silva; Amanda C L Melo; Priscila Silva; Manoela Tiago; Alisson L Matsuo; Luiz Juliano; Maria A Juliano; et al. (PLoS ONE)
The increased incidence, high rates of mortality and few effective means of treatment of malignant melanoma, stimulate the search for new anti-tumor agents and therapeutic targets to control this deadly metastatic disease. In the present work the antitumor effect of arazyme, a natural bacterial-derived metalloprotease secreted by Serratia proteomaculans, was investigated. Arazyme significantly reduced the number of pulmonary metastatic nodules after intravenous inoculation of B16F10 melanoma cells in syngeneic mice. In vitro, the enzyme showed a dose-dependent cytostatic effect in human and murine tumor cells, and this effect was associated to the proteolytic activity of arazyme, reducing the CD44 expression at the cell surface, and also reducing in vitro adhesion and in vitro/in vivo invasion of these cells. Arazyme treatment or immunization induced the production of protease-specific IgG that cross-reacted with melanoma MMP-8. In vitro, this antibody was cytotoxic to tumor cells, an effect increased by complement. In vivo, arazyme-specific IgG inhibited melanoma lung metastasis. We suggest that the antitumor activity of arazyme in a preclinical model may be due to a direct cytostatic activity of the protease in combination with the elicited anti-protease antibody, which cross-reacts with MMP-8 produced by tumor cells. Our results show that the bacterial metalloprotease arazyme is a promising novel antitumor chemotherapeutic agent.